Analisis Pengembangan Sarana Dan Prasarana Museum Kepresidenan Republik Indonesia Balai Kirti Dalam Meningkatkan Kualitas Pelayanan - Mumin, Alfiana; Saragih, Charles Parnauli; Rainanto, Bambang Hengky (Jurnal Ilmiah Pariwisata Kesatuan, 2025)
This study is a qualitative research aimed at analyzing the development of facilities and infrastructure of the Presidential Museum of the Republic of Indonesia, Balai Kirti, as a strategy to enhance the quality of service to visitors. The research method employed is SWOT analysis, gathering data through direct observation, interviews, and literature review. The analysis results indicate that the development of facilities and infrastructure is crucial in improving the quality of service at Balai Kirti Museum. Physical infrastructure upgrades, such as building renovations, improved accessibility, and provision of adequate facilities, have enhanced visitor experiences. Additionally, the integration of information technology in information presentation and visitor interaction is also a significant factor in improving service quality. The findings underscore the importance of continuously updating and improving museum facilities and infrastructure to meet visitor expectations and needs. Sustainable development in this regard will help enhance the museum's reputation, increase visitor numbers, and strengthen its contribution to promoting Indonesian culture and history. KeyWords: Tourist Attractions, Facilities and Infrastructure, Service Quality.